An Empirical Examination of Success Model SAS Application on Teritory of Bengkulu Treasury Office - Puji Astuti; Willy Abdillah (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2016)
This study examines determinants of successful of SAS application by reviewing user perception that adapted successful model of information system developed by DeLone and McLean (1992), which system quality, information quality, system use, user satisfaction, and individual impact. Primary data is obtained by questionaries filled by 100 respondents from units in the teritory of of treasury office of Bengkulu. Data analyzed by using Partial Least Square (PLS) as one of the alternative methods of Structural Equation Modeling (SEM). The results show that quality of the system and quality of information affects user satisfaction but did not affect use of the system. Use of the system affected satisfaction of user and level satisfaction of user would affect the use of the system. User satisfaction affects the impact of the individual.Keywords: Individual Impact, Information Quality, Information Systems Success, System Quality, System Use, User Satisfaction